2008
DOI: 10.1097/fjc.0b013e3181824d59
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Protects the Heart From Ischemia-Reperfusion Injury via COX-2-Derived PGI2

Abstract: There is an accumulating body of data to suggest that estrogen mediates its cardioprotective effects via cyclooxygenase activation and synthesis of prostaglandins (PG), specifically PGI2. We hypothesized that inhibition of COX-2 would prevent estrogen's cardioprotective effects after myocardial ischemia-reperfusion. Acute treatment with 17beta-estradiol (E2; 20 microg/rabbit) increased COX-2 protein expression and activity in the myocardium. To determine the effects of COX-2 inhibition on infarct size after E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…For example, in the cardiovascular system, COX-2 usually exerts beneficial effects. As previously demonstrated, the cardioprotective effects of estrogen, zileuton and atorvastatin are mediated by COX-2 (27,29,30). In accordance with a previous study (2), our data demonstrated that exposure to CoCl 2 markedly reduced COX-2 expression in the HPASMCs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, in the cardiovascular system, COX-2 usually exerts beneficial effects. As previously demonstrated, the cardioprotective effects of estrogen, zileuton and atorvastatin are mediated by COX-2 (27,29,30). In accordance with a previous study (2), our data demonstrated that exposure to CoCl 2 markedly reduced COX-2 expression in the HPASMCs.…”
Section: Discussionsupporting
confidence: 81%
“…COX-2 is a multifunctional protein, whose roles are complex and ambivalent in different models, mediating either neuronal toxicity or cardiac protection (27,28). For example, in the cardiovascular system, COX-2 usually exerts beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of COX-2 overexpression are complicated and ambivalent in different models, mediating either cytotoxicity or cytoprotection (Booth et al, 2008;Carnieto et al, 2009;Ito et al, 2003;Kwak et al, 2010;Oh et al, 2010;Tu et al, 2009;Yun et al, 2009). Some studies indicated that inhibition of COX-2 activation attenuated ischemic neuronal injury, characterized by a decrease in cerebral infarction and CA1 hippocampal neuron death (Dore et al, 2003;Nakayama et al, 1998), while other reports showed that during cardiotoxicity induced by ischemia-reperfusion (I/R), up-regulation of COX-2 expression obviously possessed protective effects (Booth et al, 2008;Kwak et al, 2010). However, the role of COX-2 in hypoxic injury of skin remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive expression of COX-2 in cardiomyocytes also represents a protective mechanism against reperfusion injury [150]. Protective effects of oestrogen in ischaemia ⁄ reperfusion have been suggested to be mediated by activation of COX-2 and subsequently prostaglandin I-2 [151]. Cardioprotective effects of a 5-lipoxygenase inhibitor have been shown to be mediated by COX-2 because of protein kinase C activation [152].…”
Section: Myocardial Perfusion Defects In Bartter and Gitelman Syndrommentioning
confidence: 98%